Factors adopting internet banking among consumer of Bank Islam Malaysia Berhad / Nur Aishah Muhammad (Faculty of Business Management, 2007)
Internet banking has become the latest delivery channel for banking services due to the reaction from globalization and liberalization of financial services. Malaysian banks are desperately embracing this new distribution channel to prepare themselves for the competition which is alarming in the near future. Thus, Bank Islam Malaysia Berhad should not only be quick to provide this facility but also to encourage customers to migrate to this system. This research mainly focuses on what factors really influent the adoption or rejection to using Internet banking among consumer of BIMB which are in terms of customer awareness, the infrastructures provided, customer's knowledge and resistance to change. Besides, this study also examined whether or not there is a correlation between respondents' demographic elements and their acceptance level of Internet banking. In completing this research, personal interviews and survey were utilized. Cluster sampling was used. The sample for this survey was drawn from 70 residents who have individual accounts in BIMB. This study revealed that awareness about the benefits of using Internet banking and the security it offers stand out as being the main drivers to the adoption of Internet banking among the consumer of BIMB. In contrary, lack of knowledge on how to use the banking site is the major factor of why some consumers are still using the conventional style of banking. Some suggestions and recommendations were given that could help in rapid migration of customers to Internet banking, resulting in considerable savings in operating costs for bank.